Human herpes virus 8-unrelated primary effusion lymphoma-like lymphoma: report of a rare case and review of the literature - BOZKURT, SÜHEYLA (WILEY-BLACKWELL PUBLISHING, INC, 2009)
Primary effusion lymphoma (PEL) is a very rare type of lymphoma usually confined to the body cavities predominantly in immunosupressed patients infected with human herpes virus 8 (HHV-8). The new term for HHV-8 independent PEL is HHV8-unrelated PEL-like lymphoma. We describe an 89-year-old human immunodeficiency virus (HIV)-negative male patient with HHV8-unrelated PEL-like lymphoma in the pleura. No hepatosplenomegaly or lymphadenopathy was detected. Chest radiography and computed tomography revealed right pleural effusion, but no evidence of tumor mass or lymph node enlargement. Cytological analysis of the pleural effusion revealed a high-grade lymphoma with round nuclei, prominent nucleoli and abundant cytoplasm with immunophenotypes positive forCD45, CD30, CD38, CD7 and CD71. Because of the advanced age, no chemotherapy was given. Effusion resolved spontaneously. One year after the diagnosis, a new pleural effusion developed at the left side. Following thoracentesis and pleurodesis, the patient remained in complete remission for 40 months. To date, 30 cases of HHV8-unrelated PEL-like lymphoma/HIV negative have been reported in the literature. The outcome of the HHV8-unrelated PEL-like lymphoma patients who were HIV negative seems to be better than HIV- and HHV-8-positive PEL.
Keywords: Primary effusion lymphoma; human herpes virus 8-unrelated primary effusion lymphoma-like lymphoma; human immunodeficiency virus; HEPATITIS-C VIRUS; HIV-SERONEGATIVE PATIENT; LIVER-CIRRHOSIS; NEGATIVE PATIENT; CELL LYMPHOMA; DNA-SEQUENCES; BODY-CAVITY; PHENOTYPE; IMMUNODEFICIENCY; DIAGNOSIS